Acoustic environments of intensive care units during the COVID-19 pandemic. (October 2022) - Song, Ziwei; Lee, Pyoung-Jik; Hampton, Thomas
Highlights: Noise levels in all the patient rooms were more than the WHO guidelines, varying from 51.1 to 60.3 dBA. Most dominant noise sources were talking/voices, door-closing, footsteps, and general activities. Footsteps became an unexpected dominant noise source during the pandemic. Talking/voices produced the highest maximum median values of the sound exposure level (SEL) and the maximum noise level at all sites. Abstract: This study aims to investigate the typical noise levels and noise sources in an intensive care unit (ICU) during the COVID-19 pandemic. Acoustic experiments were conducted over 24 hrs in patient wards and at nurse stations in four Chinese hospitals. From the measurements, noise levels and sources were analysed in terms of the A-weighted equivalent sound pressure levels ( L Aeq ) and A-weighted maximum Fast time-weighted sound pressure levels ( L AFmax ) over three different time periods during the day (i.e. day, evening and night). Overall, noise levels ( L Aeq ) for 24 hrs in all hospitals exceeded the World Health Organisation's (WHO) guide levels, varying from 51.1 to 60.3 dBA. The highest maximum noise level reached 104.2 dBA. The single-bedded wards (side rooms) were quieter than multi-bedded wards, and night time noise levels were quieter than daytime and evening across all hospitals. It was observed that the most dominant noise sources were talking/voices, door-closing, footsteps, and general activities (e.g. noise from cleaning equipment and cutlery sound). Footsteps became an unexpected dominant noise source during the pandemic because of the staff's disposable shoe covers which made footsteps noisier. Patient alarms and coughing varied significantly between patients. Talking/voices produced the highest maximum median values of the sound exposure level (SEL) and the maximum noise level at all sites. Noise levels in all the patient rooms were more than the WHO guidelines. The pandemic control guidelines had little impact on the noise levels in the ICUs.